2024
DOI: 10.3389/fnmol.2024.1335404
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profile analysis in spinal cord injury rats with transplantation of menstrual blood-derived stem cells

Longju Qi,
Wenwei Jiang,
Wenhua He
et al.

Abstract: IntroductionMenstrual blood-derived stem cells (MenSCs) are vital in treating many degenerative and traumatic disorders. However, the underlying molecular mechanisms remain obscure in MenSCs-treating spinal cord injury (SCI) rats.MethodsMenSCs were adopted into the injured sites of rat spinal cords at day 7 post surgery and the tissues were harvested for total RNA sequencing analysis at day 21 after surgery to investigate the expression patterns of RNAs. The differentially expressed genes (DEGs) were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Nerve cells have poor regenerative ability and cannot be cured after being damaged; therefore, treatment and rehabilitation after SCI are challenging ( 102 ). Differentially expressed lncRNAs play a regulatory role in SCI, providing new ideas for its treatment ( 103 ). Notably, menstrual blood-derived stem cells (MenSCs) have important therapeutic effects in degenerative and traumatic diseases, such as premature ovarian failure in mice ( 104 ) and cutaneous wound ( 105 ).…”
Section: Research Progress On Lncrnas In Scimentioning
confidence: 99%
See 1 more Smart Citation
“…Nerve cells have poor regenerative ability and cannot be cured after being damaged; therefore, treatment and rehabilitation after SCI are challenging ( 102 ). Differentially expressed lncRNAs play a regulatory role in SCI, providing new ideas for its treatment ( 103 ). Notably, menstrual blood-derived stem cells (MenSCs) have important therapeutic effects in degenerative and traumatic diseases, such as premature ovarian failure in mice ( 104 ) and cutaneous wound ( 105 ).…”
Section: Research Progress On Lncrnas In Scimentioning
confidence: 99%
“…Compared with SCI rats, rats treated with MenSCs exhibited significant upregulation of 89 lncRNAs and other RNAs, and significant downregulation of 65 lncRNAs and other RNAs. The lncRNA-miRNA-mRNA and circRNA-miRNA-mRNA ceRNA networks of SCI indicated that the role of lncRNAs in SCI may be mediated by a large interconnected regulatory network ( 103 ). Liu et al ( 106 ) examined changes in the expression of lncRNAs in the proximal tissue of the T10 layer at different time points during the right hemisection of T10 laminectomy.…”
Section: Research Progress On Lncrnas In Scimentioning
confidence: 99%